Niet alleen om de rubber: Over Baťa, Tsjechen en Slowaken in Nederlands-Indië en het beeld van Nederlands-Indië in Tsjechoslowakije - Sklenářová, Sylva; Engelbrecht, Wilken (Acta Neerlandica, 2016)
Czechoslovakia was a new state that emerged in 1918. It combined the former Kingdom of the Bohemian Crown and former Felvidék – Upper-Hungary. In the period between the two World Wars, and especially after 1930 when the Czechoslovak shoe concern Baťa started its presence in Dutch East-Indies, a couple of novels by Dutch writers has been translated into Czech. Most of them were written by Madelon Székely-Lulofs and Johan Fabricius, the latter even visited Czechoslovakia in 1934. These novels and practical travel stories mainly by Czech entrepreneurs formed the picture of Dutch EastIndies in the mind of Czechoslovak people. Because of a lack of Dutch technic graduates, Dutch authorities recruited engineers from elsewhere, especially from Central Europe. Thus, between the beginning of the 20th century and the end of Dutch East-Indies (1949) some 80 to 100 Czechoslovaks were living in the colony in 1949. Most of them didn’t receive Dutch nationality. In 1939, they were considered to be citizens of the so-called Protectorate Bohemia and Moravia. When the Japanese occupied the colony in 1941, the Protectorate government tried to repatriate its citizens and asked Japanese authorities to spare Czechs. The Japanese treated them then as “non-belligerent enemies”. Most Czechs didn’t accept the offer to stay outside the concentration camps and either entered the camps as did their Dutch colleagues, or even participated in the very little and weak resistance against the Japanese. A very special Czech presence was the factory PT Sepatu Bata built by the Czechoslovak concern Baťa in 1939 that was interested in Indonesian rubber and saw also possibilities to enter the East-Indian market.